2020
DOI: 10.3390/toxics8040126
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Zebrafish Embryo Toxicity Assay and the General and Behavioral Embryo Toxicity Assay as New Approach Methods for Chemical Screening

Abstract: The movement away from mammalian testing of potential toxicants and new chemical entities has primarily led to cell line testing and protein-based assays. However, these assays may not yet be sufficient to properly characterize the toxic potential of a chemical. The zebrafish embryo model is widely recognized as a potential new approach method for chemical testing that may provide a bridge between cell and protein-based assays and mammalian testing. The Zebrafish Embryo Toxicity (ZET) model is increasingly rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The EC 10 and EC 50 values for larval growth obtained in the present study agree with previous research carried out with sea urchin embryos for CPF (Bellas et al 2005 ; Buono et al 2012 ) and BPA (Kiyomoto et al 2006 ; Özlem and Hatice 2008 ; Tato et al 2018 ), reporting effects at similar concentrations than those reported here. However, no information is available on the toxicity of TPHP on sea urchin embryos and limited toxicological information has been obtained on early stages of aquatic organisms, mainly on zebrafish ( Danio rerio ), reporting effects within the range of 40–29,600 μg/l (geometric mean: 650 μg/l) (e.g., Isales et al 2015 ; Jarema et al 2015 ; Achenbach et al 2020 ). These effect concentrations are, in general, higher than concentrations detected in seawater for these substances (usually < 0.5 μg/l) (Campillo et al 2013 ; Liu et al 2018 ; Salgueiro-González et al 2019 ), although higher concentrations can be present close to main pollution sources or, in the case of plastic additives, close to high plastic debris accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…The EC 10 and EC 50 values for larval growth obtained in the present study agree with previous research carried out with sea urchin embryos for CPF (Bellas et al 2005 ; Buono et al 2012 ) and BPA (Kiyomoto et al 2006 ; Özlem and Hatice 2008 ; Tato et al 2018 ), reporting effects at similar concentrations than those reported here. However, no information is available on the toxicity of TPHP on sea urchin embryos and limited toxicological information has been obtained on early stages of aquatic organisms, mainly on zebrafish ( Danio rerio ), reporting effects within the range of 40–29,600 μg/l (geometric mean: 650 μg/l) (e.g., Isales et al 2015 ; Jarema et al 2015 ; Achenbach et al 2020 ). These effect concentrations are, in general, higher than concentrations detected in seawater for these substances (usually < 0.5 μg/l) (Campillo et al 2013 ; Liu et al 2018 ; Salgueiro-González et al 2019 ), although higher concentrations can be present close to main pollution sources or, in the case of plastic additives, close to high plastic debris accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…The use of zebrafish embryos is one of the most attractive, leading toxicology models in this field, and it constitutes a suitable alternative for the use of small laboratory animals, such as rats or mice, due to short analysis times, short life cycle and transparency of embryos, and, importantly, zebrafish share approximately seventy percent protein-coding genes with humans. [63][64][65] Thus, zebrafish (Danio rerio) teratogenicity assays are commonly used for the prediction of the embryotoxic effects of chemicals, including new drug candidates. The images of zebrafish (Danio rerio) embryos treated with and without the compound 7 are presented in Fig.…”
Section: Application Of Compounds 5-7 As Anticancer Agentsmentioning
confidence: 99%
“…Polysaccharide extracts have also been tested on living organisms, for example, on zebrafish embryos, in the so-called zebrafish embryo toxicity test (ZFET) [ 25 ]. Zebrafish have become an alternative model to rodent toxicity in in vivo assays [ 26 , 27 , 28 ]. This model provides important features, namely, rapid external embryonic development, a small size, optical transparency, a large number of offspring, and genetic similarities to humans [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%